The Buton Sultanate Fortresses in Eastern Indonesia: A Trace of the Sultanate’s Military Supremacy - Suseno, Sandy (KnE Social Sciences, 2022)
Archaeological remains in the form of fortresses are found in Southeast Celebes. These forts are spread across the islands. The existence of these forts cannot be separated from the narrative of the Buton Sultanate in Southeast Celebes. The fortresses are located in the Barata territory of the Buton Sultanate. These fortresses marked the military triumph of the Buton Sultanate as a maritime empire in the eastern Indonesia archipelago. However, in the historiography of Indonesia, the Buton Sultanate is not recorded as one of the major maritime powers in eastern Indonesia. This research aimed to detail the existence of the fortresses of the Buton Sultanate to demonstrate their significance using an archaeological and historiography approach. These fortresses are evidence of the supremacy of the maritime power of the Buton Sultanate in the archipelago. In revealing the traces of its military supremacy, this research demonstrates the significance of the Buton Sultanate as a maritime empire. Keywords: fortresses, Buton Sultanate, military, maritime